Answer:
The rule for g is:
![g(x)=1.3(x^2-1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/5el6xinkjurdrl9pscrxpszk1ctf4obory.png)
Explanation:
The equation of the function f(x) is given by:
![f(x)=x^2+4x](https://img.qammunity.org/2019/formulas/mathematics/middle-school/2cnjhcvahlj2xuv1yy8jl4rmlm8cihurkq.png)
Now, it is given that:
The graph of h is a translation 3 units up and 2 units right of the graph of f(x).
This means that:
![h(x)=f(x-2)+3](https://img.qammunity.org/2019/formulas/mathematics/middle-school/psrukl7u1ljpdk7ssbi11w0eqixc8yzwfz.png)
Hence, we have the equation for the function h(x) as:
![h(x)=(x-2)^2+4(x-2)+3\\\\h(x)=x^2+4-4x+4x-8+3\\\\h(x)=x^2+4-8+3\\\\h(x)=x^2-1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/bakt405vycka8ujze3v0ie3yn5x11wcs0k.png)
Also, g(x) is 130% of h(x).
i.e.
![g(x)=130\% \ of \ h(x)\\\\g(x)=1.3h(x)\\\\g(x)=1.3(x^2-1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vmvi234zvban2m2uj9bztwgxumnpdtjnfu.png)